2020
DOI: 10.1038/s41929-020-0482-5
|View full text |Cite
|
Sign up to set email alerts
|

Tuning water reduction through controlled nanoconfinement within an organic liquid matrix

Abstract: The growing hydrogen-economy requires accelerating the hydrogen evolution reaction. The water dissociation step (Volmer step) has been proposed as a main kinetic limitation, but the mechanisms at play in the electrochemical double-layer are poorly understood. This is due to the ambivalent role of water: it acts both as a reactant and as a solvent. Here we propose to confine water inside an organic liquid matrix in order to isolate the sole role of water as a reactant. We observe the formation of aqueous-rich n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
136
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 69 publications
9
136
0
Order By: Relevance
“… 2020 3 656 663 . 4 The composition and size of aqueous-rich nanodomains inside an organic matrix were tuned by changing the supporting electrolyte and water concentration. The reactivity of the system was shown to vary significantly with this nanostructure.…”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“… 2020 3 656 663 . 4 The composition and size of aqueous-rich nanodomains inside an organic matrix were tuned by changing the supporting electrolyte and water concentration. The reactivity of the system was shown to vary significantly with this nanostructure.…”
Section: Key Referencesmentioning
confidence: 99%
“…Once the hydrophilic Li + cations were identified as the species that promote the HER the most when the water content is low, we decided to investigate the effect of interactions taking place at long range on the HER. 4 In a first step, fixing the LiClO 4 concentration at 100 mM while increasing the water content from 1% to 10% by mass was found not to modify the onset potential at which the water reduction occurs, as shown in the linear sweep voltammogram in Figure 4 a. Molecular dynamics simulations of the electrolyte between two carbon electrodes held at a constant applied voltage showed that water is mostly coordinated to Li + cations at both 1% and 10% by mass (see Figure 4 c,d). Increasing the amount of water in the system leads only to the formation of some small clusters of free water surrounding the Li + –(H 2 O) x adducts ( Figure 4 c).…”
Section: Confining Water To Study Its Electrochemical Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A water molecule is considered to be free when it is not coordinated to any lithium ion, i. e . when the corresponding shortest distance is larger than the first minimum of the RDF (but it is worth noting that in WiS they remain partly coordinated to other water molecules through an extended hydrogen‐bond network, which will affect their reactivity as well) [54] . The amount of free water molecules is shown in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…At the negative electrode it is also expected that the formation of the protective SEI will be more difficult for these salts. Nevertheless, simulation of electrode/electrolyte interfaces would be necessary to confirm this point [54] …”
Section: Resultsmentioning
confidence: 99%